GEOTECHNICAL STUDIES OF CAUSES OF FAILURE OF SOME SECTIONS OF FARIN GADA – ZABOLO ROAD, JOS- PLATEAU, NORTH CENTRAL NIGERIA. - I.E., ABALAKA,; O.K., LIKKASON (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Damaged sections of Farin Gada – Zabolo road were thoroughly investigated to know the causes by examining the geotechnical properties of the soils found along the failed and the un-failed sections. The engineering tests carried out include sieve analysis, Atterberg limits, natural moisture content, shear strength test and compaction tests. Fifteen (15) samples were investigated in all. Nine (9) samples were gotten from the damaged sections of the road while six (6) samples were gotten from the undamaged sections of the road. The results of the laboratory tests showed that for Atterberg limit tests, the plasticity index for the soils in the damaged section ranged from 20.0 – 29.4% which implies a high swelling potential indicative of clay while that of the undamaged road section ranged from 6.5 –13.7% which implies a low swelling potential indicative of sand/gravel. The sieve analysis results showed that the damaged road section had a range of 54 -73% of the soil material passing through sieve no 200 which are very fine materials indicative of clay while the undamaged road sections had a range of 8 -30% of soil materials passing through sieve no 200 indicatives of the fact that majority of the soil in the area are mainly sand/gravel. For compaction, soils collected at the damaged sections of the road had maximum dry density that ranged from 1.480 – 1.687g/cm3 and optimum moisture content values that ranged from 21.2 – 27.8%. In the undamaged sections of the road, the maximum dry density values ranged from 1.842- 1.947g/cm3 while their optimum moisture content ranged from 8.56 – 12.02%. The low MDDs and the OMCs in the damaged sections of the road are indicative of the fact that the soils have low bearing capacities and cannot be used as construction materials except they are well compacted and stabilized appropriately. In terms of shear strength, the angle of internal friction ranged from 12.0 – 29.00 while the cohesion ranged from 2.0 -14.0 which is indicative of cohesive soils since none of the shear parameters is zero. Cohesive soils have low shear strength and fails easily under construction. The results show that high clay/ silty nature of the area is responsible for the road failure. This makes the soil unsuitable as road construction materials and hence, the there is need for stabilization during the reconstruction and rehabilitation of the road. .